2020
DOI: 10.1042/bsr20200308
|View full text |Cite
|
Sign up to set email alerts
|

Which sample type is better for Xpert MTB/RIF to diagnose adult and pediatric pulmonary tuberculosis?

Abstract: Objective: This review aimed to identify proper respiratory-related sample types for adult and pediatric pulmonary tuberculosis (PTB), respectively, by comparing performance of Xpert MTB/RIF when using bronchoalveolar lavage (BAL), induced sputum (IS), expectorated sputum (ES), nasopharyngeal aspirates (NPA) and gastric aspiration (GA) as sample. Methods: Articles were searched in Web of Science, PubMed, and Ovid from inception up to June 29, 2020. Pooled sensitivity and specificity were calculated, each with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…One meta-analysis reported that expectorated sputum was the best sample type for diagnosing adult PTB, with a pooled sensitivity of 90%, while the pooled sensitivity of expectorated sputum in children was only 14%. Although GA specimens were suitable for childhood TB diagnosis, the sensitivity (80%) was slightly lower than that of sputum in adults ( Lyu et al, 2020 ). The pretreatment protocol applied to GA specimens in this study was adapted from that of sputum samples; whether this method is suitable and can affect the detection rate of the EasyNAT MTC assay remains unclear.…”
Section: Discussionmentioning
confidence: 94%
“…One meta-analysis reported that expectorated sputum was the best sample type for diagnosing adult PTB, with a pooled sensitivity of 90%, while the pooled sensitivity of expectorated sputum in children was only 14%. Although GA specimens were suitable for childhood TB diagnosis, the sensitivity (80%) was slightly lower than that of sputum in adults ( Lyu et al, 2020 ). The pretreatment protocol applied to GA specimens in this study was adapted from that of sputum samples; whether this method is suitable and can affect the detection rate of the EasyNAT MTC assay remains unclear.…”
Section: Discussionmentioning
confidence: 94%
“…The added value of Xpert in non-sputum sample types was highly variable, ranging from 8% in blood to 100% in CSF. These findings from the Myanmar NTP suggest that Xpert can be effectively used to great affect among pediatric populations (who often require gastric lavage as a clinical sample 21 ), and PLHIV who can have higher rates of extrapulmonary TB disease requiring non-pulmonary samples for Xpert diagnosis. While we had no data on the reasons for different sample types being collected for each patient, we assumed based on NTP protocols, that alternative samples were collected only when sputum samples were not obtainable or when extrapulmonary disease was indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the expense of NAAT, it is important to use sample types that offer the best diagnostic performance. Meta-analysis for the Xpert MTB/RIF assay concluded that expectorated sputum provided the best diagnostic performance, i.e., 90% sensitivity and 98% specificity, in adults [57] . Sensitivity and specificity for bronchoalveolar lavage and induced sputum was 87% and 91% and 86% and 97%, respectively.…”
Section: Active Tuberculosismentioning
confidence: 99%